2019
DOI: 10.1002/jcb.28422
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun triple‐layered PLLA/gelatin. PRGF/PLLA scaffold induces fibroblast migration

Abstract: The function of fibroblast cells in wounded areas results in reconstruction of the extra cellular matrix and consequently resolution of granulation tissue. It is suggested that the use of platelet-rich plasma can accelerate the healing process in nonhealing or slow-healing wounds. In this study, a simple and novel method has been used to fabricate an electrospun three-layered scaffold containing plasma rich in growth factor with the aim of increasing the proliferation and migration of fibroblast cells in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 41 publications
(69 reference statements)
1
20
0
Order By: Relevance
“…Furthermore, the correlation between gene expression, release profile, and cell behavior displayed that the scaffold containing PRGF can be potentially used as a wound dresser. 5 MTT results showed an increase in the number of active cells on days 1, 3, and 7 in the TCPS group, while reducing viable cells was observed after day 7. In addition, the cells showed a proper proliferation with reasonable speed on these scaffolds until day 14.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Furthermore, the correlation between gene expression, release profile, and cell behavior displayed that the scaffold containing PRGF can be potentially used as a wound dresser. 5 MTT results showed an increase in the number of active cells on days 1, 3, and 7 in the TCPS group, while reducing viable cells was observed after day 7. In addition, the cells showed a proper proliferation with reasonable speed on these scaffolds until day 14.…”
Section: Discussionmentioning
confidence: 85%
“…The multi-layered scaffolds, similar to skin architecture, are employed as potential engineered skin substitutes applicable to wound care. 5 Efficient genome engineering tools and reliable reporter cell lines are invaluable tools to investigate the role and behavior of cells during the treatment processes. Sitespecific gene integration at pre-defined safe harbour loci facilitates rapid generation of stable cell lines with limited transgene silencing and few detrimental effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this type of gelatin-based scaffolds, in addition to drug transport and use for tissue engineering, the migration of certain cells can also be induced or favored. This is the case in the study of Piran et al [47] that synthesized electrospun three-layered scaffold with plasma enriched with growth factor to promote the migration and growth of fibroblast, which is a very important aspect in the regeneration of wounds.…”
Section: Electrospun Nanofibers For Drug Delivery Applicationmentioning
confidence: 99%
“…Gelatin nanofibers (like collagen) have been used in biomedical applications such as cosmetics, wound dressing, tissue engineering, surgical treatments, etc [34]. Gelatin nanofibers (having sufficient mechanical properties to be used in these applications as nanofibrous mats) have been electrospun for ultrathin nanofibers [34][35][36][37][38][39][40][41][42][43][44]. These authors also reported that the properties of these nanofibers can be tailored as per requirements by optimizing input parameters such as voltage, viscosity, distance between the spinneret and rotating drum collector, and flow rate.…”
Section: Introductionmentioning
confidence: 99%